(untitled) (Revista Direitos Humanos e Democracia, 2025)
This text investigates the impact of the loss of human rights experienced during Jair Bolsonaro’s government and the consequences of this on the subjectivity of social actors linked to the defense of human rights in Tocantins and São Paulo. The research method was interviews with leaders who defend human rights and the data was analyzed using a mixed method of discourse analysis and analysis of narratives of suffering. Two forms of suffering emerge in the research; the first concerns the consequences of what we can call "starvation policies", which would be determined by the systematic cuts in public funds and financing during the period from 2018 to 2022. The second is related to hate speech, both from the former president and the Bolsonaro digital militias. Feelings of anxiety, fear, impotence, discouragement and depression were recounted by the interviewees as a consequence of this social and political situation. However, various actions of resistance, struggle, elaboration of losses and ways of coping with this condition appear.